PENGARUH PENERAPAN METODE PEMBELAJARAN AKTIF TIPE COURSE REVIEW HOREY TERHADAP PEMAHAMAN KONSEP DAN MOTIVASI BELAJAR MATEMATIKA SISWA KELAS VIII.6 SMP NEGERI 14 PADANG - Seprinelfi, Feny; Rismen, Sefna; Mardiyah, Ainil (Pendidikan Matematika, 2014)
ABSTRACTÂ This research were motivated by students comprehension of mathematical concept and studentsâ motivation to learn mathematics that still low. The purpose of this research were to determine whether studentsâ comprehension of mathematical concept by implementing course review horey methods was better than implementing conventional learning and to determine studentsâ motivation to learn mathematics after implementing course review horey methods in class VIII of SMP Negeri 14 Padang. This was an experimental research which used purposive sampling. The sample was VIII.6 as experiment class and VIII.4 as control class. The instrument used were final test and motivation questionnaire. The dataÂ  were analyzed by using t-test for final test and percentage techniques for motivation questionnaire. Based on the result of data analysis, it was revealed that sample has normally distributed and homogeneus. Hypothesis test results obtained that Â was greater than Â then Â was rejected. Questionnaire analysis result obtained that score of all indicators with positive statement was increased. It can be conclude that studentsâ comprehension of mathematical concept by implementing course review horey methods was better than implementing conventional learning and studentâs motivation after implementing course review horey method was increased in class VIII.6 of SMP Negeri 14 Padang school year 2013/2014.